Reading comprehension input benefits on vocabulary acquisition of ESL adult students - Hernández Porras, Francinie (2021)
This article focuses on the positive effects reading comprehension has on the vocabulary acquisition process of ESL adult learners. The purpose is to show students the benefits of reading comprehension and motivate them to read more. The article is a literature review of different authors who talk about reading comprehension effects and methods.